Data Encryption and Authetication Using Public Key Approach - Nagaraj, Srinivasan; Raju, G.V.S.P. (Universitas Ahmad Dahlan, 2015)
Today various numbers ofÂ Â diverse applications that include e- payments in secure commerce and payment applications to provide securityÂ for their communications and transactions by protecting passwords. Encryption is a fundamental tool for the protection of sensitive information. The purpose is to use encryption is privacy for preventing disclosure or confidentiality in during communications. In this paper, we proposed a new method which is based onÂ the Eulerâs TotientÂ theorem Â to produce a set of numbers Â that Â encrypt the data stream and then we used our proposed method Â usingÂ an ECC approach to generate theÂ signature keyÂ which is added to encrypt data before transmission and decryption operation andÂ a signatureÂ can verify at the receiver site.